Reversible Live‐Cell Labeling with Retro‐engineered HaloTags Enables Long‐Term High‐ and Super‐Resolution Imaging. Issue 18 (10th March 2023) - Holtmannspötter, Michael; Wienbeuker, Eike; Dellmann, Timo; Watrinet, Isabelle; Garcia‐Sáez, Ana J.; Johnsson, Kai; Kurre, Rainer; Piehler, Jacob
Abstract: Self‐labeling enzymes (SLE) such as the HaloTag have emerged as powerful tools in high and super‐resolution fluorescence microscopy. Newly developed fluorogenic SLE substrates enable imaging in the presence of excess dye. To exploit this feature for reversible labeling, we engineered two variants of HaloTag7 with restored dehalogenase activity. Kinetic studies in vitro showed different turnover kinetics for reHaloTagS (≈0.006 s −1 ) and reHaloTagF (≈0.055 s −1 ). Imaging by confocal and stimulated emission depletion microscopy yielded 3‐5‐time enhanced photostability of reHaloTag labeling. Prominently, single molecule imaging with reHaloTags enabled controlled and stable labeling density over extended time periods. By combination with structured illumination, simultaneous visualization of single molecule diffusion and organellar dynamics was achieved. These applications highlight the potential of reHaloTag labeling for pushing the limits of advanced fluorescence microscopy techniques. Abstract : Retro‐engineered HaloTags (reHaloTags) show substrate exchange in the seconds‐to‐minutes regime due to their restored dehalogenase activity. Using fluorogenic substrates, reHaloTags outperform the standard HaloTag7 in bleaching resistance and control of labeling density. Single molecule tracking and localization microscopy particularly benefits from these new tags, opening exciting possibilities for untangling protein dynamics over extended time.